Social and geographical features of the formation of the intellectual potential of Chernivtsi oblast - Bilous, Yuriі (Human Geography Journal, 2020)
The article studies the peculiarities of the formation of intellectual potential of Chernivtsi oblast by analyzing its components, and also analyzes the participation of students in student competitions in subjects and in the competition-defense of research works of students of the Small Academy of Sciences of Ukraine, as well as their results. The analysis of gender peculiarities of students’ participation in the researched competitions is carried out, and also the geographical factors influencing formation of intellectual potential are considered.In 2019, there were 372 preschool educational institutions, 403 general secondary education institutions, 16 vocational education institutions and 16 higher education institutions in Chernivtsi oblast, which provided relevant educational services and formed the intellectual potential of the region. In Chernivtsi oblast in the 2019-2020 academic year, 1,814 students took part in the III stage of student academic competitions. The largest number of participants was observed at the academic competition in geography, Ukrainian language and literature, history and biology. In total, 845 participants took top places. The best results were shown by students of Chernivtsi, Storozhynets AH, Novoselytsia AH and students of Kelmentsi rayon. As for the all-Ukrainian competition-defense of research works, in 2020 378 students took part in the competition, of which 187 participants took top places. The best results, as in the academic competition, were demonstrated by students from Chernivtsi and Putyla rayon. Territorial differences in the development of intellectual potential occur under the influence of economic, demographic, legal, environmental, natural and other factors. The following indicators correlate most with the number of points scored by teams: the number of educational institutions in the rayon; share of new type of institutions (gymnasiums, lyceums, etc.); language of instruction.The gender structure of participants and winners of these intellectual competitions deserves a special attention. Girls predominate in the gender structure of participants and winners of the academic competition and defense competition in most subjects, especially in subjects of the philological and philosophical cycle, while the number of boys predominates in the academic competitions of the physical and mathematical cycle. Thus, in Chernivtsi oblast there is a significant differentiation between territorial and administrative units according to the results of the III stage of student academic competitions in basic disciplines and the competition-defense of scientific works of students-members of the Small Academy of Sciences.